Qara-Chattan Rock slide in Pira-Magroon Anticline, Northeastern Iraq - Ahmad, Kamal Haji Karim; Hamasur, Ghafir Ameen; Mohamad, Sherzad Tofiq (Sulaimani Journal for Pure and Applied Sciences, 2000)
This paper deals with a rock failure from Pira-Magroon Mountain, Northeastern Iraq. Field study and graphical representation showed that this failure is a rockslide. Being located near Qara-Chattan village, we named this phenomenon as Qara-Chattan Rockslide. About 200 million tons of rock materials are slided from the elevation of 29000 meters above sea level to the elevation of 1000 meters. The slide rock debris now rested on a gently sloping plain near the village and forming a tongue like hill about 50 meters high. Many geomorphologic features and slide activating factors are also discussed as well as stereonet analysis of the rockslide.